2015
DOI: 10.1111/fcp.12144
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of statin therapy on oxidative damage in heart tissue of hypercholesterolemic rabbits

Abstract: The aim of this study was to investigate the effects of a high-cholesterol diet in the presence and absence of statin on Cu-Zn-superoxide dismutase (Cu,Zn-SOD), malondialdehyde (MDA), protein carbonyl (PCO), and nitric oxide (NO) of blood and heart tissue, the antioxidant activity of serum paraoxonase-1 (PON-1), and on the blood lipid profile of rabbits. The animals were divided into four groups each of which included 10 rabbits. Rabbits in group 1 received a regular rabbit chow diet (normal diet) for 8 weeks;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
3
2
0
Order By: Relevance
“…However, the pretreatment of rats with atorvastatin attenuated testosterone-induced MDA generation and enhanced GSH and SOD activity. This finding corroborates the report of antioxidant property of atorvastatin in heart tissues [35]. In contrast, pretreatment of rats with celecoxib or pioglitazone failed to enhance the antioxidant enzyme activity in the prostate compared with vehicle-testosterone-treated.…”
Section: Discussionsupporting
confidence: 91%
“…However, the pretreatment of rats with atorvastatin attenuated testosterone-induced MDA generation and enhanced GSH and SOD activity. This finding corroborates the report of antioxidant property of atorvastatin in heart tissues [35]. In contrast, pretreatment of rats with celecoxib or pioglitazone failed to enhance the antioxidant enzyme activity in the prostate compared with vehicle-testosterone-treated.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, similar to tamoxifen, administration of simvastatin was associated with an increase in PON1 activity in serum of mice of D2 group. Consistent with this finding, Sozer et al showed that atorvastatin can increase PON1 activity in hypercholesterolemic rabbits, the same effect has also been shown in dyslipidemic patients . Although we did not evaluate the mechanism for the increase in PON1 activity in our study, it has been shown that simvastatin can modulate gene expression of this enzyme .…”
Section: Discussionsupporting
confidence: 89%
“…Despite the increased GSH content in the heart of hypercholesterolemic mice, this improvement in antioxidant defense did not translate into a decrease in oxidative damage, as evidenced by a trend of increasing carbonyl levels in cardiac tissue of mice fed a high cholesterol diet. This finding agrees with previous studies, in which animals with dietinduced hypercholesterolemia exhibit high carbonyl levels in heart tissue (Sozen et al 2018, Sozer 2015. Hypercholesterolemia was also related to increased oxidative damage to lipids (AlSaad et al 2020, Sozer 2015 and DNA (Chtourou et al 2015) in cardiac tissue.…”
Section: Impact Of Hypercholesterolemic Diet and Aunp Treatment On Ox...supporting
confidence: 92%
“…Hypercholesterolemia was also related to increased oxidative damage to lipids (AlSaad et al 2020, Sozer 2015 and DNA (Chtourou et al 2015) in cardiac tissue. Of particular interest, some of these negative effects of hypercholesterolemia on oxidative stress have been prevented by treatment with substances with antioxidant properties (AlSaad et al 2020, Sozer 2015, Chtourou et al 2015.…”
Section: Impact Of Hypercholesterolemic Diet and Aunp Treatment On Ox...mentioning
confidence: 99%